2012
DOI: 10.1007/s11010-012-1264-4
|View full text |Cite
|
Sign up to set email alerts
|

Chronic hydrogen-rich saline treatment reduces oxidative stress and attenuates left ventricular hypertrophy in spontaneous hypertensive rats

Abstract: In hypertensive animals and patients, oxidative stress represents the primary risk factor for progression of left ventricular hypertrophy. Recently, it has been demonstrated that hydrogen, as a novel antioxidant, can selectively reduce hydroxyl radicals and peroxynitrite anion to exert therapeutic antioxidant activity. In the current study, we explored the effect of chronic treatment with hydrogen-rich saline (HRS) on left ventricular hypertrophy in spontaneously hypertensive rats (SHR). The 8-week-old male SH… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
26
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(31 citation statements)
references
References 38 publications
1
26
1
Order By: Relevance
“…Based on previous studies and our data, the possible mechanism of H2 on the therapy of AA might be as follows. Firstly, it was reported that H2 inhibited NF-▩B activation, which causes a transcriptional up-regulation of inflammatory cytokines, such as TNF-α, IL-6, IFN-γ etc [24,34,35]. These cytokines was also found decreased in the H2 treated groups in our experiment, indicating NF-▩B as a possible target for the regulating effect of H2 on the cytokines microenvironment.…”
Section: Discussionsupporting
confidence: 57%
See 1 more Smart Citation
“…Based on previous studies and our data, the possible mechanism of H2 on the therapy of AA might be as follows. Firstly, it was reported that H2 inhibited NF-▩B activation, which causes a transcriptional up-regulation of inflammatory cytokines, such as TNF-α, IL-6, IFN-γ etc [24,34,35]. These cytokines was also found decreased in the H2 treated groups in our experiment, indicating NF-▩B as a possible target for the regulating effect of H2 on the cytokines microenvironment.…”
Section: Discussionsupporting
confidence: 57%
“…Meanwhile, our research determined that hydrogen can protect mice from GVHD by regulating TNF-α, IL-2, IL-10 [17]. Hydrogen was also demonstrated to be able to down-regulate levels of various cytokines, including TNF-α, IFN-γ, IL-1, IL-6, IL-12 in different models [24,25,26]. These cytokines play important roles in AA.…”
Section: Discussionmentioning
confidence: 99%
“…Drinking H 2 -rich water blocks cardiac fibrosis induced by left kidney artery ischemia/reperfusion injury (Zhu et al, 2011). H 2 -rich saline injection also inhibits ischemia/reperfusion (Sun et al, 2009), or hypertension-mediated cardiac remodeling (Wang et al, 2011; Yu and Zheng, 2012). However, the effects of intraperitoneal injection of H 2 on cardiac hypertrophy induced by β-adrenoceptor stimulation have not yet been clarified.…”
Section: Discussionmentioning
confidence: 99%
“…These findings confirm that the anti-hypertrophic effect of H 2 is partially achieved through blocking ROS-dependent MAPKs signaling. Yu Yongsheng et al has reported that H 2 -rich saline inhibits cardiac hypertrophy in spontaneous hypertensive rats (SHRs) via blocking NF-κB activity (Yu and Zheng, 2012). H 2 -rich saline reduces myocardial reperfusion injury and improves heart function through down-regulating the expression of Akt and GSK3β (Yue et al, 2015), and blocking autophagy in myocardial tissue (Pan et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…The protective effects of H 2 on cardiac hypertrophy were also confirmed in SHR. H 2 -rich saline attenuates left ventricular hypertrophy in SHR via suppressing inflammatory process, abating oxidative stress, preserving mitochondrial function, and inhibition of Ang II levels in left ventricles locally might also be involved [51]. …”
Section: The Effects Of H2 In Heart Diseasesmentioning
confidence: 99%